Morphological characterization of Agave angustifolia and its conservation in Guerrero, Mexico - Barrientos Rivera, Guillermina; Esparza Ibarra, Edgar León; Segura Pacheco, Hector Ramón; Talavera Mendoza, Oscar; Sampedro Rosas, Maria Laura; Hernández Castro, Elías (Revista Mexicana de Ciencias Agrícolas, 2019)
Agave angustifolia has a wide morphological variation, which often makes its taxonomy difficult. The differentiation between Agave species is made from homologous and independent morphological characteristics, whose variation can be ontogenetic and genetic. The objective of this research was to characterize the morphology of A. angustifolia called ‘sacatoro’ from the state of Guerrero. The research was conducted from 2016 to 2017, in six populations of A. angustifolia and two populations as control, A. angustifolia Haw and A. cupreata. 32 stem and leaf variables of mother plants and shoots were measured for each specimen, according to the technical guide for the varietal description of Agave spp. The data were analyzed using main components (ACP) and hierarchical agglomerative grouping (AJA). The variables that allowed to discern the populations were: shape, edge, color and texture of the leaf, striae on lateral spines and length of the terminal spine, all with a positive correlation. The results obtained from the ACP and the AJA allowed observing the relationship between variables and specimens based on the morphological attributes shared by the species studied. Despite the morphological variation between maguey sacatoro and A. angustifolia Haw, a close positive relationship between both is shown. So it is inferred that the phenotypic characteristics that sub grouping the maguey sacatoro, could show as a result a possible variant of A. angustifolia Haw that would allow to locate taxonomically this group to contribute to the ordering of the Agave genus and its conservation.
Keywords: Agave angustifolia; conservation; maguey sacatoro; phenotypic